Survey of submissions on the Sharm El-Sheik joint work on implementation on agriculture and food security - CGIAR Initiative on Low-Emission Food Systems (2023)
The four-year Sharm El-Sheik joint work on implementation on agriculture and food security (SSJW) was adopted at COP27 of the United Nations Framework Convention on Climate Change (UNFCCC). It takes off from the Koronivia Joint Work on Agriculture (KJWA), which was established in 2017 at COP23 held in Bonn, Germany.